تعرض المراهقين للأعمال المقدمة عبر المنصات الرقمية وعلاقته بهويتهم الثقافية - عبدالسيد، سمر نعيم جيد; نحلة، عمرو محمد عبدالله; عبدالمطلب، نادر محمد علي (جامعة عين شمس - كلية الدراسات العليا للطفولة, 2022)
يهدف البحث إلى الكشف عن أبعاد الهوية الثقافية الأكثر تأثيرًا بالمنصات الرقمية من وجهة نظر المراهقين، ورصد كثافة متابعة المراهقين للأعمال المقدمة عبر المنصات الرقمية، تنتمى هذه الدراسة إلى الدراسات الوصفية التي تعتمد على منهج المسح، تم تطبيق الدراسة على عينة عمديه من المراهقين الذين يشاهدون الأعمال الدرامية عبر منصة نتفلكس من الفرقة الدراسية الأولى بالجامعات المصرية، وقوامها ٤٥٠ مفردة، حيث طبقت استمارة الاستبيان، ومقياس الهوية الثقافية على عينة الدراسة، وتمثلت أهم نتائج الدراسة الحالية فيما يلي أن نسبة من يتابعون المنصات الرقمية بصورة ضعيفة من إجمالي مفردة عينة الدراسة بلغت 27.1%، وبلغ نسبة من يتابعون المنصات الرقمية بكثافة متوسطة ٤٦,٤%، بينما بلغت نسبة من يتابعون المنصات الرقمية بدرجة كثيفة 26.4%، وجاء في مقدمة المنصات الرقمية الأكثر متابعة "نتفلكس Netflix " بنسبة بلغت 88.2% من إجمالي مفردات عينة الدراسة، يليها بالترتيب الثاني منصة "واتش ات Watch it " حيث جاءت بنسبة ٧٣,٨%، وجاءت أبعاد الهوية الثقافية الأكثر تأثيرًا بالمنصات الرقمية والتي ظهر في مقدمتها بعد "اجتماعي" بنسبة بلغت ٧٩,١% من إجمالي مفردات عينة الدراسة، يليها بالترتيب الثاني البعد "اللغوي"، حيث جاءت بنسبة 75.3% من إجمالي مفردات عينة الدراسة، كذلك بالترتيب الثالث بعد "العادات والتقاليد"، حيث جاءت بنسبة 71.3% من إجمالي مفردات عينة الدراسة، تليها بالترتيب الرابع بعد "ديني"، حيث جاءت بنسبة ٧١,١% من إجمالي مفردات عينة الدراسة، أما البعد "التاريخي" فجاء الترتيب الخامس بنسبة ٣٦,٠% من إجمالي مفردات عينة الدراسة، بينما جاء بالترتيب السادس والأخير "بعد الوطني" بنسبة ٢٤,٧% من إجمالي عينة المراهقين، يوجد فرق دال إحصائيًا بين متوسطات درجات الذكور ومتوسطات درجات الإناث ممن يتابعون المنصات الرقمية وتأثيرها على الهوية الثقافية لديهم، توجد علاقة ارتباطية دالة إحصائيًا بين أسباب تعرض المراهقين للأعمال المقدمة على المنصات الرقمية وتأثيرها على الهوية الثقافية لديهم، توجد فروق ذات دلالة إحصائية بين مستويات تعرض المراهقين للأعمال المقدمة على المنصات الرقمية وتأثيرها على الهوية الثقافية لديهم. The research aims to reveal the dimensions of cultural identity that most affect digital platforms from the perspective of adolescents, and to monitor the intensity of adolescents’ follow up to the works presented via digital platforms. The drama, via the Netflix platform, from the first academic year in Egyptian universities, consisting of 450 items, as the questionnaire and the cultural identity scale were applied to the study sample, The most important results of the current study were as follows The percentage of those who follow digital platforms weakly out of the total sample of the study amounted to 27.1%, and the percentage of those who follow digital platforms with a medium intensity 46.4%, while the percentage of those who follow Digital platforms in a dense degree 26.4%, and Netflix came at the forefront of the most followed digital platforms, with a rate of 88.2% of the total vocabulary of the study sample, followed by Watch iT platform, where it came with a percentage of 73.8% The dimensions of cultural identity that have the most impact on digital platforms, which appeared in the forefront of the "social" dimension, amounted to 79.1% of the total vocabulary of the study sample, followed by the "linguistic" dimension, which came in the second order, with 75.3% of The total vocabulary of the study sample, also in the third order after "habits and traditions", where it came with 71.3% of the total vocabulary of the study sample, followed by the fourth place after "religious", where it came with 71.1% of the total vocabulary of the study sample. The historical dimension, the fifth rank came with a percentage of 36.0% of the total vocabulary of the study sample, while it came in the sixth and last rank "after the national" with a percentage 24.7% of the total sample of adolescents, There is a statistically significant difference between the average scores of males and the average scores of females who follow digital platforms and their impact on their cultural identity. They have, there are statistically significant differences between the levels of adolescents' exposure to work presented on digital platforms and their impact on their cultural identity.
Keywords: المنصات الرقمية -- مرحلة المراهقة -- الهوية الثقافية -- الانفتاح الثقافي